2017
DOI: 10.1523/jneurosci.1554-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Wnt9a Can Influence Cell Fates and Neural Connectivity across the Radial Axis of the Developing Cochlea

Abstract: Vertebrate hearing organs manifest cellular asymmetries across the radial axis that underlie afferent versus efferent circuits between the inner ear and the brain. Therefore, understanding the molecular control of patterning across this axis has important functional implications. Radial axis patterning begins before the cells become postmitotic and is likely linked to the onset of asymmetric expression of secreted factors adjacent to the sensory primordium. This study explores one such asymmetrically expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 47 publications
10
38
0
Order By: Relevance
“…At this dose, several known Wnt target genes are upregulated, suggesting that Wnts can promote specification of medial sensory identity to both the IHCs and their associated supporting cells . When Wnt9a is overexpressed in the chicken cochlea, there is a similar increase in the tall hair cells (homologous to IHCs in the medial domain) and a nearly complete loss of the short hair cells (homologous to OHCs in the lateral domain) . The loss of these short hair cells is consistent with the effects brought about by Wnt activation in the mouse.…”
Section: Grns Related To Wnt Signalingsupporting
confidence: 64%
See 2 more Smart Citations
“…At this dose, several known Wnt target genes are upregulated, suggesting that Wnts can promote specification of medial sensory identity to both the IHCs and their associated supporting cells . When Wnt9a is overexpressed in the chicken cochlea, there is a similar increase in the tall hair cells (homologous to IHCs in the medial domain) and a nearly complete loss of the short hair cells (homologous to OHCs in the lateral domain) . The loss of these short hair cells is consistent with the effects brought about by Wnt activation in the mouse.…”
Section: Grns Related To Wnt Signalingsupporting
confidence: 64%
“…Both Kremen1 and GSK‐3β could prevent an excess number of IHCs and pillar cells; however, Wnt inhibition does not imply that Kremen1 and Gsk‐3β play a role in specifying hair cells/pillar cells but merely regulate their numbers. Therefore, the hypothesis that Wnts help specify IHCs/tall hair cells is still valid, even though Wnts are unlikely to be the only regulator of Atoh1 expression (Figures and ). As the field progresses, new regulators of Atoh1 will be identified.…”
Section: Grns Related To Wnt Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we also expected Sema3D to show a similar distribution to Sema3F , and that Nrp2 would be in cochlear ganglion neurons. We further hypothesized that the down regulation of both genes in the presence of exogenous Wnt9a contributed to the increase in afferent innervation previously described (Munnamalai et al, ). In accordance with our RNA sequencing data, in situ hybridization shows a severe reduction of both Sema3D and Nrp2 in Wnt9a‐infected BPs (Figure e,g).…”
Section: Discussionmentioning
confidence: 79%
“…Neuronal cell adhesion molecule (NrCAM) has been shown to associate with Nrp2 (Julien et al, ) and recent work in the mouse inner ear has shown that it is involved in limiting ribbon synapses in the HCs, likely through inhibiting synapse formation or promoting pruning (Harley et al, ). RNA sequencing data failed to detect NrCAM transcripts in the chicken BP at E6 (Munnamalai et al, ), although this time point precedes synapse formation in this organ.…”
Section: Discussionmentioning
confidence: 98%